The use of an integrated grammar-genre-based writing approach to teach business writing skills - Michael, Bartholomew (2013)
The abstract of thesis presented to the Senate of Asia e University in fulﬁlment of the requirement for the degree of Doctor of Philosophy. Teaching intermediate Business English writing skills without a proper module or approach to a group of Low English Proﬁciency (LEP) students, who face serious problems in terms of language and writing skills, can be very challenging and demanding to teachers. Thus, to overcome these problems, this researcher had conducted an intensive, 6-month research with the objective of creating and testing out a speciﬁc, comprehensive and integrated writing approach called the Integrated Grammar-Genre-based Business Writing Approach (IGGBWA). This approach was created based on sound grammar, genre and writing theories and concepts. Based on this approach, a prototype module called the Integrated Grammar-Genre-based Business Writing Module (IGGBWM) was developed to teach the London Chamber of Commerce and Industry’s English for Business Level Two programme. This research was also aimed at studying changes in the attitude and motivational level of the students after being exposed to the IGGBWM. An intact group of 38 students was exposed to the IGGBWA and IGGBWM through an Action Research programme by way of a Mixed Method approach. Data was collected via four quantitative instruments (Language Ability, Sentence Maturity, Business Document Writing Skills and survey Questionnaire) and four written tests. Another two sets of qualitative inﬂmments (Group Journal Writing and Written Response Questionnaire) were used to furnish the relevant data to shed more light on the quantitative Mean T-unit Length was used to measure the development in syntactic